2021
DOI: 10.1016/j.pedneo.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The etiologic, microbiologic, clinical and outcome characteristics of immunocompetent young children <2 years of age hospitalized with acute neutropenia

Abstract: Background: To describe the etiologic, microbiologic, clinical and outcome characteristics of acute neutropenia (absolute neutrophil count, ANC, <1.5 Â 10 9 /L) in hospitalized immunocompetent children. Methods: Serious bacterial infections (SBI) were defined as culture-positive blood, urine, cerebrospinal fluid, articular fluid or stool infections, alveolar pneumonia, Brucellosis and Rickettsiosis. Results: 431/671 (64.2%) healthy infants and children hospitalized with acute neutropenia were <2 years of age; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…25,26 Higher rates of bac te rial infec tions have been reported in stud ies focused on hos pi tal ized neutropenic patients (12.7%-14.9%, with 1 study dem on strat ing 0%), 27 which may have resulted from the admis sion of sicker patients and the infec tious envi ron ment of the pop u la tion, as bru cel losis and rick ett sia, bac te rial infec tions known to be asso ci ated with neutropenia, were reported eti ol o gies in 3 out of 4 of these inpa tient-only stud ies. [28][29][30][31] The con clu sion from these stud ies is that the risk of bac te rial infec tion in the out pa tient set ting for the well-appearing pediat ric patient with iso lated and unsus pected neutropenia is low and sim i lar to patients with nonneutropenic fever. Screening for bac te rial infec tion, includ ing a blood cul ture, a uri nal y sis with urine cul ture, and, for symp tom atic patients, a chest x-ray, is suggested, but aggres sive man age ment includ ing admis sion and empiric anti bi ot ics may not be nec es sary for all patients.…”
Section: Fever Man Age Ment In the Newly Diag Nosed Neutropenic Patientmentioning
confidence: 99%
“…25,26 Higher rates of bac te rial infec tions have been reported in stud ies focused on hos pi tal ized neutropenic patients (12.7%-14.9%, with 1 study dem on strat ing 0%), 27 which may have resulted from the admis sion of sicker patients and the infec tious envi ron ment of the pop u la tion, as bru cel losis and rick ett sia, bac te rial infec tions known to be asso ci ated with neutropenia, were reported eti ol o gies in 3 out of 4 of these inpa tient-only stud ies. [28][29][30][31] The con clu sion from these stud ies is that the risk of bac te rial infec tion in the out pa tient set ting for the well-appearing pediat ric patient with iso lated and unsus pected neutropenia is low and sim i lar to patients with nonneutropenic fever. Screening for bac te rial infec tion, includ ing a blood cul ture, a uri nal y sis with urine cul ture, and, for symp tom atic patients, a chest x-ray, is suggested, but aggres sive man age ment includ ing admis sion and empiric anti bi ot ics may not be nec es sary for all patients.…”
Section: Fever Man Age Ment In the Newly Diag Nosed Neutropenic Patientmentioning
confidence: 99%
“…These findings were not novel and similar to that previously reported in the medical literatures. 7 However, the study still gave us the specific findings that after one-month follow-up period, the resolution of neutropenia occurred in almost half of them without any association with age subgroups and the severity of neutropenia. Additionally, nasal washings and PCR for respiratory viruses were positive in 47.4% of tested patients, and respiratory syncytial virus, adenovirus, parainfluenza, and influenza A were found to be the main viruses associated with acute neutropenia.…”
mentioning
confidence: 93%
“…Tschernin et al described the etiology and clinical characters of acute neutropenia in hospitalized immunocompetent children aged under two years. 7 Besides culture-based and serologic techniques, the molecular approaches including multiplex real-time polymerase chain reaction (PCR) were also performed for the identification of 12 respiratory viruses. They found that young children aged under two years, especially aged 0e3 months, was the majority of hospitalized patients diagnosed with acute neutropenia.…”
mentioning
confidence: 99%
“…Recent studies have reported that acute neutropenia occurs more commonly in young infants (<2 years of age) than in older children (16.7% of these children have severe neutropenia and 12.7% show SBI). 9,11.…”
mentioning
confidence: 99%
“…9,11. Brucellosis and rickettsiosis, which affect up to 34% of patients, are the most common infections observed among SBIs. 9,[11][12][13]…”
mentioning
confidence: 99%